Probiotics and vitamins modulate the cecal microbiota of laying hens submitted to induced molting - Wang, Chunyang; Shan, Honghu; Chen, Hui; Bai, Xindong; Ding, Jingru; Ye, Dongyang; Adam, Fathalrhman Eisa Addoma; Yang, Yawei; Wang, Juan; Yang, Zengqi (Frontiers in Microbiology, 2023)
Induced molting enables laying hens to relax, restore energy and prolong the laying hen cycle, resolving problems such as poor egg quality and minimizing economic losses caused by rising global feeding costs. However, traditional molting methods may disrupt gut microflora and promote potential pathogens infections. This study used a customized additive with a mixture of probiotics and vitamins to induce molting and examine the cecal microbiota post molting. A total of two hundred 377 day-of-ISA Brown laying hens were randomly assigned to 4 groups: non-molt with basal diet (C), 12-day feeding restriction (FR) in earlier-molting (B), feed again to 27.12% egg production in middle-molting (A) and reach second peak of egg production over 81.36% in post-molting (D). Sequencing 16S rRNA to analyze cecal microbial composition revealed that there is no significant change in bacterial community abundance post-molting. In contrast to group C, the number of potentially harmful bacteria such as E. coli and Enterococcus was not found to increase in groups B, A, or D. This additive keeps cecal microbiota diversity and community richness steady. In cecal contents, hens in group B had lower Lactobacillus, Lachnospiraceae and Prevotellaceae (vs C, A and D), no significant differences were found between post-molting and the non-molting. Furthermore, cecal microbiota and other chemicals (antibodies, hormones, enzymes, etc.) strongly affect immunological function and health. Most biochemical indicators are significantly positively correlated with Prevotellaceae, Ruminococcaceae and Subdoligranulum, while negatively with Phascolarctobacterium and Desulfovibrio. In conclusion, the additive of probiotics and vitamins improved the cecal microbiota composition, no increase in the associated pathogenic microbial community due to traditional molting methods, and enhances hepatic lipid metabolism and adaptive immunological function, supporting their application and induced molting technology in the poultry breeding industry.